Perancangan Sistem Pakar Untuk Diagnosa dan Rekam Riwayat Kerusakan Laptop Menggunakan Metode Dempster Shafer - Meutia Hilda, Atiqah; Rifki Alfiansyah, Mohamad; Jafar Elly, Muhammad (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
Laptops are one of the most widely used computer devices because they have a minimalist and practical design so they can be taken anywhere. Using a laptop for a long period of time sometimes results in various types of damage with a variety of specific symptoms. The availability of technician laptop service locations is not always available within 24 hours. Based on preliminary data, 58% of users do not know the actual location of the damage to their laptop, while 42% of users already know the location of the damage to their laptop, and 48% of users will first find out the cause of the damage on the internet, the other 30% will immediately take it to a service center.. Goal. of this system is to create an Expert System for Diagnosing Laptop Damage and recording the damage history based on a website, making it easier for laptop users to find out where the damage to their laptop is based on the symptoms they experience. System testing was carried out using alpha and beta testing which resulted in an effectiveness test of 85.81, this shows that the system can make it easy for laptop users to find the location of the damage to their laptop based on symptoms.